2021
DOI: 10.1177/00207640211020036
|View full text |Cite
|
Sign up to set email alerts
|

National identification, a social cure for COVID-19? Evidence from 67 countries

Abstract: Background: Social distancing and mass quarantines were implemented worldwide in response to the current COVID-19 pandemic. Prior research has shown that such measures bear negative consequences for population mental health and well-being. Conversely, a growing body of evidence suggests that feeling positively identified with a group is associated with physical and mental health benefits. Aims: This study tested whether national identification could promote wellbeing and physical health during the COVID-19 pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 87 publications
2
19
0
Order By: Relevance
“…These complementary theories, now recognized as the social identity approach, were initially an explanation for intergroup attitudes and behavior (e.g., prejudice, discrimination, cooperation), but new research has shown social identities also have a strong impact on individual health and well-being because of the close connection between the self and the group (for reviews, see Haslam et al, 2009 ; Jetten et al, 2017 ). For instance, just during the COVID-19 pandemic alone, recent data from 67 countries suggest stronger identification with one’s nation predicted more positive well-being ( Bonetto et al, 2021 ) and stronger adherence to recommended health behaviors ( Van Bavel and Boggio, 2020 ). Despite an emerging research agenda that has wielded social identities as a tool for improving individual health and well-being ( Jetten et al, 2017 ), comparatively little research has examined the impact of broader, more inclusive social identifications (e.g., human identity, global identity) on personal health behaviors that have implications for collective health.…”
Section: Introductionmentioning
confidence: 99%
“…These complementary theories, now recognized as the social identity approach, were initially an explanation for intergroup attitudes and behavior (e.g., prejudice, discrimination, cooperation), but new research has shown social identities also have a strong impact on individual health and well-being because of the close connection between the self and the group (for reviews, see Haslam et al, 2009 ; Jetten et al, 2017 ). For instance, just during the COVID-19 pandemic alone, recent data from 67 countries suggest stronger identification with one’s nation predicted more positive well-being ( Bonetto et al, 2021 ) and stronger adherence to recommended health behaviors ( Van Bavel and Boggio, 2020 ). Despite an emerging research agenda that has wielded social identities as a tool for improving individual health and well-being ( Jetten et al, 2017 ), comparatively little research has examined the impact of broader, more inclusive social identifications (e.g., human identity, global identity) on personal health behaviors that have implications for collective health.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between national identification and risk perception in the COVID-19 context has been recognised to be of growing importance. Some see the possibility of harnessing shared identifications to motivate preventive behaviour or accelerate pro-active responses (Bonetto et al, 2021;Vignoles et al, 2021). Our findings suggest that national identification accentuates awareness of danger of new viral infections.…”
Section: Variant Dangerousnessmentioning
confidence: 74%
“…The positive effects of the “social cure” provided by group memberships emerged in coping with the uncertainty and threat induced by COVID-19 [ 4 , 28 ]. A study conducted in 67 countries reported that national identification was positively related to mental well-being as individuals dealt with the loneliness elicited by anti-contagion policies such as lockdowns and mass quarantines [ 29 ]. Other studies provided additional confirmation of the potential of having multiple identifications.…”
Section: Literature Review and Research Overviewmentioning
confidence: 99%